Speaking for Academic Purposes Course: An Analysis of Language Functions - Sebastianus Menggo; I Made Suastra; Made Budiarsa; Ni Nyoman Padmadewi (e-Journal of Linguistics, 2019)
Speaking as the most demanding skill to be mastered in the ESL/EFL teaching context. Thisis caused by the prime priority of students who want to study English in order to be able to use Englishfor communicative purposes. Knowledge of language functions has a vital role in supporting a speaker tobe more involved in the real interaction. The aims of this study are to identify and analyze the kinds oflanguage functions and how their use in the speaking for academic purposes course. This study wasconducted at Universitas Katolik Indonesia Santu Paulus Ruteng, Flores. The data were taken from 33English department students who were doing the English speaking exercises at the speaking for academicpurposes course. The data were collected through observation, field note and recording during eightmeetings on October- November 2018 and only language functions utterances of those respondents wereanalyzed. The recorded utterances are expected to be representative of the whole the language functions.Utterances produced by respondents were recorded precisely by the researchers. The result showed thatthere are five types of language functions found, namely interactive function, informative function,manipulative function, motivative function and directive functions. Those functions are reciprocal.Speaking practitioners are suggested to provide the knowledge of language functions in the speakinglearning process.